A study on the interpersonal behaviours of trainee teachers with their students during teaching practicum / Ahmad Irfan Jailani - Jailani, Ahmad Irfan (2014)
This study investigated the interpersonal behaviours of 85 trainee teachers from the Faculty of Education, UiTM towards their students during their teaching practicum. Questionnaire on Teacher Interaction (QTI) was used to determine the frequency of the 8 identified behaviours exhibited by the respondents. Analysis of the acquired data showed that the trainee teachers from the Faculty of Education, UiTM frequently showed behaviours which indicate understanding, friendliness and leadership qualities. The pattern of all the 8 interpersonal behaviours combined indicates that the respondents were tolerant and authoritative towards their students. The analysed data also indicate that the respondents from different programmes have different interpersonal behaviour from one another. From the results of this study, it was determined that further steps should be taken to improve the quality of interpersonal behaviours portrayed by trainee teachers.